The EORTC CAT Core—The computer adaptive version of the EORTC QLQ-C30 questionnaire. (September 2018) - Petersen, Morten Aa.; Aaronson, Neil K.; Arraras, Juan I.; Chie, Wei-Chu; Conroy, Thierry; Costantini, Anna; Dirven, Linda; Fayers, Peter; Gamper, Eva-Maria; Giesinger, Johannes M.; Habets, Esther J.J.; Hammerlid, Eva; et al.
Abstract: Background: To optimise measurement precision, relevance to patients and flexibility, patient-reported outcome measures (PROMs) should ideally be adapted to the individual patient/study while retaining direct comparability of scores across patients/studies. This is achievable using item banks and computerised adaptive tests (CATs). The European Organisation for Research and Treatment of Cancer (EORTC) Quality of Life Questionnaire Core 30 (QLQ-C30) is one of the most widely used PROMs in cancer research and clinical practice. Here we provide an overview of the research program to develop CAT versions of the QLQ-C30's 14 functional and symptom domains. Methods: The EORTC Quality of Life Group's strategy for developing CAT item banks consists of: literature search to identify potential candidate items; formulation of new items compatible with the QLQ-C30 item style; expert evaluations and patient interviews; field-testing and psychometric analyses, including factor analysis, item response theory calibration and simulation of measurement properties. In addition, software for setting up, running and scoring CAT has been developed. Results: Across eight rounds of data collections, 9782 patients were recruited from 12 countries for the field-testing. The four phases of development resulted in a total of 260 unique items across the 14 domains. Each item bank consists of 7–34 items. Psychometric evaluations indicated higher measurement precision and increased statistical power of the CAT measures compared to the QLQ-C30 scales. Using CAT, sample size requirements may be reduced by approximately 20–35% on average without loss of power. Conclusions: The EORTC CAT Core represents a more precise, powerful and flexible measurement system than the QLQ-C30. It is currently being validated in a large independent, international sample of cancer patients. Highlights: The European Organisation for Research and Treatment of Cancer (EORTC) CAT Core is an adaptive version of the EORTC QLQ-C30 questionnaire. Development of EORTC CAT Core was based on almost 10, 000 patients from 12 countries. With the computerised adaptive test (CAT), sample sizes may be reduced by 20–35% on average without loss of power. The EORTC CAT Core is a more precise, powerful and flexible measure than the QLQ-C30.